Land-cover change in the Berg River catchment : implications for biodiversity conservation - Stuckenberg, Tristan (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: Biodiversity refers to the variety of life on earth at all scales of observation. Its persistence underlies ecological and evolutionary processes and is pivotal for the sustenance and future development of human societies through the provision of ecosystem services. Especially since the industrial revolution, anthropogenic land-cover change has placed ever-increasing strain on natural systems through the destruction and degradation of habitat. The Cape Floristic Region (CFR) is a global biodiversity hot spot which contains some of the highest levels of floristic diversity and endemism on the planet. Since European settlement large swathes of this region have been transformed to facilitate socio-economic development, placing tremendous pressure on indigenous biodiversity. Due to the intimate relationship that exists between land cover and biodiversity it is possible to draw inferences on the current state of the biodiversity of an area, assess the pressures that will likely face it in the future and plan accordingly based on an analysis of land-cover change. As a means of assessing the state of biodiversity in the CFR, this thesis has developed a series of three land-cover maps for the Berg River catchment in the Western Cape province for 1986/1987, 1999/2000 and 2007 using Landsat TM and ETM+ data. Areas of natural vegetation were delineated on the land-cover maps using an object-orientated nearest neighbour supervised classification. Remnants of natural vegetation were classified according to potential vegetation boundaries described by Mucina and Rutherford’s map of the vegetation of South Africa, Lesotho and Swaziland. Contrary to initial expectations, the area occupied by natural vegetation had increased by 14%. However, considerable variation was recorded between vegetation types with certain types exhibiting marked increases in extent while others had been encroached by expanding cultivated and urban areas. An assessment of the accuracy of the 2007 land-cover map showed that significant swathes of natural vegetation were infested with alien invasive species or dominated by particularly resilient species which are not as severely affected by anthropogenic activities as other species. It is concluded that the methodology employed in this study provides a scoping mechanism by which more intensive research may be directed toward areas exhibiting significant land-cover change.